2018
DOI: 10.1253/circj.cj-18-0121
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Drug-Coated Balloons in Coronary Artery Disease Unsuitable for Drug-Eluting Stent Implantation

Abstract: For lesions that are unsuitable for stent implantation, stent-less intervention using a DCB should be considered initially. The present study also highlighted that lesion preparation is key to a successful DCB strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In all procedures, scoring balloon, Lacrosse NSE™ (Goodman Co., Ltd., Nagoya, Japan) or cutting balloon (Boston Scientific, Marlborough, MA, USA) was used for pre-dilatation under IVUS guidance. This was because previous studies have shown significantly lower incidences of major dissection in target lesions treated with the scoring balloon than with other devices, and the optimal lesion preparation using a scoring balloon is essential for ensuring a low incidence of target lesion failure after DCB treatment [14,15]. Further, appropriate lesion preparation was performed, after which, the lesion was dilated once for at least 30 s with the paclitaxel-coated (3 μg/mm 2 ) balloon catheter based on Paccocath Technology (SeQuent Please™, B. Braun Melsungen AG, Berlin, Germany) for drug delivery.…”
Section: Pci Proceduresmentioning
confidence: 99%
“…In all procedures, scoring balloon, Lacrosse NSE™ (Goodman Co., Ltd., Nagoya, Japan) or cutting balloon (Boston Scientific, Marlborough, MA, USA) was used for pre-dilatation under IVUS guidance. This was because previous studies have shown significantly lower incidences of major dissection in target lesions treated with the scoring balloon than with other devices, and the optimal lesion preparation using a scoring balloon is essential for ensuring a low incidence of target lesion failure after DCB treatment [14,15]. Further, appropriate lesion preparation was performed, after which, the lesion was dilated once for at least 30 s with the paclitaxel-coated (3 μg/mm 2 ) balloon catheter based on Paccocath Technology (SeQuent Please™, B. Braun Melsungen AG, Berlin, Germany) for drug delivery.…”
Section: Pci Proceduresmentioning
confidence: 99%
“…[5] In addition, the absence of a metallic stent and long-term polymer ensures the integrity of the vascular anatomy, which decreases hemodynamic abnormalities and shortens the duration of dual antiplatelet therapy. [6,7]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, optimal lesion pretreatment is essential for the success of the DEB-only strategy. Iijima et al showed that the use of a nonslip element balloon was effective for optimal lesion preparation before the use of the DEB due to its ability to reduce elastic recoil, traumatic vessel injury, and dissection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%